Prevalence of depression between institutionalized elderly (Research, Society and Development, 2020)
This study aims at conducting research on the prevalence of depression among institutionalized elderly people. This is a literature review, of the integrative type. To search for and select the studies, the following databases were used: PubMed, Scielo and Science direct, totaling 10 articles, published between 2016 and 2019. It was verified that there is a high percentage of depression among the elderly institutionalized, which was evidenced in the studies analyzed, where they found high rates of depression among them, which may be due to the feeling of rejection by family and friends, as well as the impediment of carrying out daily activities and leisure that bring them among many other factors. We conclude that the prevalence of depression among these institutionalized elderly is high. It is necessary to understand the main factors that lead them to the picture of depression, so that there is development of specific actions in order to improve the quality of life.